When is the observational method in geotechnical engineering favourable?. (May 2017) - Spross, Johan; Johansson, Fredrik
Highlights: Introduction of a reliability constraint on the observational method. Comparison of expected utilities of considered design options. Establishment of limits of acceptable behaviour based on target reliability. Abstract: The observational method in geotechnical engineering is an acceptable verification method for limit states in Eurocode 7, but the method is rarely used despite its potential savings. Some reasons may be its unclear safety definition and the lack of guidelines on how to establish whether the observational method is more favourable than conventional design. In this paper, we challenge these issues by introducing a reliability constraint on the observational method and propose a probabilistic optimization methodology that aids the decision-making engineer in choosing between the observational method and conventional design. The methodology suggests an optimal design after comparing the expected utilities of the considered design options. The methodology is illustrated with a practical example, in which a geotechnical engineer evaluates whether the observational method may be favourable in the design of a rock pillar. We conclude that the methodology may prove to be a valuable tool for decision-making engineers' everyday work with managing risks in geotechnical projects.